ANALISIS PASAR TENAGA KERJA DAN TINGKAT PENGANGGURAN TERBUKA DI PROVINSI NUSA TENGGARA BARAT - Mikael Silaban; Riski Anto Nainggolan; Sri Ningsih (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the dynamics of the labor market and the Open Unemployment Rate (OUR) in West Nusa Tenggara (NTB) Province during the 2020–2024 period and its projection toward 2026. This research employs a qualitative descriptive method using a secondary data analysis approach derived from Statistics Indonesia (BPS) and relevant literature. The findings indicate that the OUR in NTB has consistently declined from 4.22% in 2020 to 2.73% in 2024, remaining below the national average. However, the low unemployment rate does not fully reflect labor welfare, as it is still dominated by the informal sector, high underemployment, and skill mismatches with industry demands. Therefore, strengthening vocational education, improving human resource quality, and formalizing MSMEs are essential to promote inclusive and sustainable economic growth in the region.